Retrospective analysis of injury trends in recreational skiers and snowboarders in Erciyes Ski Centre - Özen, G.; Yilmaz, E.; Koç, H.; Akalan, C. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2018)
Purpose: The purpose of this study is to investigate the important differences in overall rates and frequency of injury cases and injury characteristics between the recreational alpine skiers and snowboarders in Erciyes Ski Centre. Methods: The data for this research was obtained from the Erciyes Ski Centre Injury Surveillance System. A total of 834 injury cases that ski patrols registered injury cases caused by recreational alpine skiing and snowboarding during the 2002 to 2017 winter seasons were respectively examined. The injury cases were grouped according to the skiing disciplines. All data were analysed using SPSS software. Results: Injury cases were 690 skiers (82.7%) and 144 snowboarders (17.3%). 397 (57.5%) male and 293 (42.5%) female were skiers and 91 (63.2%) male and 53 (36.8%) female were snowboarders. There was no statistically significant difference between the gender ratios in skiers and snowboarders (p > .05). Data analysis indicated that there were statistically significant differences in the ratios of lower and upper extremity injuries between skiers and snowboarders ( p < .05 ). Skiers suffered more lower extremity injuries while snowboarders suffered more upper extremity injuries ( p < .05 ). Contusion was the most common injuries type in both skiers and snowboarders ( p < .05) . Conclusions: The lower extremity injuries in skiers and the upper extremity injuries in snowboarders were more common with respect to body location of injuries. For both the recreational activities, contusion was the most common injury type.